EFFECT OF OZONE ENRICHMENT AND SPRAYING WITH COCONUT WATER AND MORINGA EXTRACT ON VEGETATIVE GROWTH AND YIELD OF BROCCOLI PLANT UNDER HYDROPONIC SYSTEM WITH MODIFIED NFT TECHNOLOGY - Salman, A. D.; Abdulrasool, I. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was carried out at University of Baghdad - College of Agricultural Engineering Sciences - Research Station B during the autumn season 2019-2020, in order to evaluate the effect of Ozone and the foliar application of coconut water and moringa extract on the growth of broccoli plant grown in modified NFT film technology. A factorial experiment (2*5) was carried out within Nested Design with three replicates. The ozone treatment was distributed into the main plots which consisted of oxygen (O2) and ozone (O3). The foliar application of organic nutrients were distributed randomly within each replicate including five treatments, which were the control treatment (T0), Coconut water with two concentrations of 50 (T1) and 100 ml. L-1 (T2), and Moringa leaves extract at two concentrations 2% (T3) and 4% T4. Results revealed a significant effect of interaction between the ozone and the foliar application of coconut water 100 ml. L-1 (O3T2) on the leaves content of Ca, Mg, Fe, Zn, Cu, B, Chlorophyll, plant height, leaves number, leaves area, root length, roots dry weight, number and weight of secondary  heads (24.09 ,33.16, 55.00, 56.01, 102.85, 72.01, 13.88, 9.39, 90.56, 96.56, 28.07, 24.52, 120.0, 77.48% respectively) compared to the control treatment (O2T0). Interaction between ozone enrichment and the foliar application of 4% Moringa leaves extract (O3T4) were recorded a significant increment in the main tablet weight, reached 687.33 gm.Plant-1 compared to the control treatment (O2T0). Interaction between ozone and Moringa leaves extract at 2% (O3T3) or, and coconut water 100 ml. L-1 (O3T2) had a significant increment in the total yield reached 51.07 and 50.94 tons.ha-1, respectively, compared to the control treatment (O2T0).